Reaction mechanisms of carbon dioxide, ethylene oxide and amines catalyzed by ionic liquids BmimBr and BmimOAc: a DFT study. Issue 40 (29th September 2016) - Luo, Zhoujie; Wang, Binsen; Liu, Yuan; Gao, Guohua; Xia, Fei
Abstract : The binary ionic liquids BmimBr and BmimOAc have the important electrostatic and hydrogen bond effects on the catalytic conversion of carbon dioxide, ethylene oxide and aniline to 3-phenyl-2-oxazolidionone. Abstract : The mechanisms of the one-pot conversion of carbon dioxide, ethylene oxide, and aniline to 3-phenyl-2-oxazolidionone catalyzed by the binary ionic liquids of BmimBr and BmimOAc were explored using the DFT methods. The complex reaction above comprises of two parallel reactions and a subsequent cascade reaction. DFT calculations on reaction pathways and energy profiles reveal that the electrostatic and hydrogen-bond effects of BmimBr play a crucial role in the parallel reactions for the generation of ethylene carbonate and 2-phenylamino-ethanol. Further, the subsequent cascade reaction to generate 3-phenyl-2-oxazolidinone catalyzed by BmimOAc follows a stepwise mechanism, which is more favorable than the concerted mechanism governed by BmimBr. In addition, BmimBr can accelerate the side reaction of aniline and ethylene oxide to yield a mixture of oligomers, which accords with the experimental observation. This theoretical work provides a deep insight into the catalytic roles of binary ionic liquids and also inspires us to design high efficient catalysts for the conversion of carbon dioxide further.